The Role of “Ikan Makan” and “Ikan Tacucu” to Overcome the Financial Insecurity of Purse Seine Crews Households in Maluku - Apituley, Yolanda Marla Tania Nangkah; D Hahury, Hendry; Camerling, Billy; Wenno, Max Robinson; Bawole, Dionisius (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2023)
“Ikan makan” and “ikan tacucu” are the terms found in purse seine fishing systems in Maluku which is one of the important sources in the economic sustainability of fishermen crews’ households. This study aims to: 1) Describe the meaning and function of “ikan makan” and “ikan tacucu” in the context of purse seine fisheries in Maluku, 2) Analyze the importance of “ikan makan” and “ikan tacucu” in improving the economy of purse seine crews households, and 3) Analyze the importance of “ikan makan” and “ikan tacucu” in overcoming the financial insecurity for purse seine crews households. This research was conducted by using a survey method. Data were analyzed by using qualitative and quantitative descriptive analysis. The results show that there are two patterns of the distribution of “ikan makan”; first share the fish equally among the all crews and then each of them is responsible for it; second, selling all the “ikan makan” and the money will be divided equally among all crew members. The income of the crews from the sale of “ikan makan” in fish season is IDR 69,000 – 166,000/trip and in no fish season fish IDR 44,000 – 111,000/trip. Income from the sale of “ikan makan” during the fish season and no fish season are not able to overcome the households financial insecurity and only to reduce or suppress it.